Perioral soft tissue change after isolated mandibular surgery for asymmetry patients. Issue 6 (June 2017) - Jeon, Eun-Gyu; Lee, Sung-Tak; Kwon, Tae-Geon
Abstract: Introduction: This study was intended to determine whether isolated mandibular surgery for the correction of asymmetry could also change perioral soft tissue asymmetry. Patients and methods: Skeletal class III patients who had undergone mandibular set-back surgery were included. The subjects were composed of two groups with (n = 20) or without (n = 30) menton (Me) deviation over 4 mm. The perioral lip landmarks were analyzed on three-dimensional image from cone-beam computed tomography taken before and 6 months after the operation. The bilateral and inter-group differences and pre- and post-operative changes were statistically analyzed. Results: The corner of mouth on the deviated side was 1.9 mm shorter vertically than that on the contralateral side in patients with asymmetry. After mandibular surgery, the deviated Me moved 5.5 mm to the contralateral side and the lip canting was corrected by 2.4° in the asymmetry group. The degree of Me deviation was significantly correlated with the degree of midline asymmetry in perioral soft tissue landmarks including subnasale, upper and lower lip midline. The predictor variable that affected the changes in lip cant was the surgical correction of Me deviation. Discussion: The correction of chin deviation by isolated mandibular surgery could significantly improve the subnasal and lip asymmetry.